Immunoglobulin heavy chain gene expression in peripheral blood B lymphocytes. - Huang, C (1992)
cDNA libraries for IgM heavy chain variable regions were prepared from unmanipulated peripheral blood lymphocytes of two healthy people. Partial sequencing of 103 clones revealed VH gene family use and complete CDR3 and JH sequences. The libraries differed in the two subjects. In one person's cDNA the VH5 family was overexpressed and the VH3 family underexpressed relative to genomic complexity. In the second person's cDNA, VH3 was most frequently expressed. In both libraries, JH4 was most frequent. VH segments of several clones were closely related to those in fetal repertoires. However, there was also evidence of mutation in many cDNAs. Three clones differed from the single nonpolymorphic VH6 germline gene by 7-13 bases. Clones with several differences from VH5 germline gene VH251 were identified. CDR3 segments were highly diverse. JH portions of several CDR3's differed from germline JH sequences. 44% of the clones had DH genes related to the DLR and DXP families, most with differences from germline sequences. In 11 DLR2-related sequences, several base substitutions could not be accounted for by polymorphism. Thus, circulating IgM-producing B cell populations include selected clones, some of which are encoded by variable region gene segments that have mutated from the germline form.